A ELOQUÊNCIA DO VERNÁCULO NA AURORA DO HUMANISMO | THE ELOQUENCE OF THE VERNACULAR IN THE DAWN OF HUMANISM - Beccari, Alessandro Jocelito (Estudos Linguísticos e Literários, 2016)
A oposição entre Renascimento e Idade Média pode ser pensada em termos linguísticos: os humanistas opuseram-se aos estudiosos medievais ao criticar o mau uso que estes haviam feito do latim e as consequentes distorções das ideias dos antigos. Para perseguir essa questão, este artigo discute diferentes concepções de gramática em escritos de pensadores proto-humanistas e escolásticos. Adotam-se aqui as perspectivas de Koerner (1989) e Murray (1998), teóricos da Historiografia Linguística. Abstract: The opposition between the Renaissance and the Middle Ages can be considered in linguistic terms: humanists opposed medieval scholars by criticizing their misuse of Latin and consequent distortions of the ideas of the ancients. This article pursues this question by discussing different conceptions of grammar in the writings of proto-humanist scholars and medieval thinkers. The perspectives adopted here are based on the works of linguistic-historiographical theorists Koerner (1989) and Murray (1998).